2017
DOI: 10.1007/s12975-017-0539-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Exposure to Cell-Free Hemoglobin Following Preterm Intraventricular Hemorrhage: Causal in Cerebellar Damage?

Abstract: Decreased cerebellar volume is associated with intraventricular hemorrhage (IVH) in very preterm infants and may be a principal component in neurodevelopmental impairment. Cerebellar deposition of blood products from the subarachnoid space has been suggested as a causal mechanism in cerebellar underdevelopment following IVH. Using the preterm rabbit pup IVH model, we evaluated the effects of IVH induced at E29 (3 days prior to term) on cerebellar development at term-equivalent postnatal day 0 (P0), term-equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
3
20
1
Order By: Relevance
“…(Lekic T et al, 2015). GMH is a devastating neonatal stroke characterized as neuroinflammation, hydrocephalus, primary and secondary brain injury, neurodevelopmental delay (Agyemang et al, 2017). Furthermore, neuroinflammation is also a trigger of secondary injury after GMH.…”
Section: Discussionmentioning
confidence: 99%
“…(Lekic T et al, 2015). GMH is a devastating neonatal stroke characterized as neuroinflammation, hydrocephalus, primary and secondary brain injury, neurodevelopmental delay (Agyemang et al, 2017). Furthermore, neuroinflammation is also a trigger of secondary injury after GMH.…”
Section: Discussionmentioning
confidence: 99%
“…These morphological changes were most prominent at P0 and P2, coinciding in time with the finding of decreased EGL proliferation. The vulnerability of Purkinje cell development to insults associated with preterm birth have been recently shown in rat pups exposed to neonatal hyperoxia and also in preterm rabbit pups with preterm cerebral intraventricular hemorrhage exhibiting delayed maturation of Purkinje cells and decreased granular precursor cell proliferation [26, 27]. The cerebellar Purkinje cells have several key functions relating to EGL proliferation, and subsequent inward cell migration and Purkinje cell secretion of the transcription factor Shh are key for EGL precursor cell proliferation [12, 13, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In a preterm rabbit pup model of IVH, it has been observed that extracellular Hb and its downstream metabolites cause structural damage of the choroid plexus [ 84 , 85 , 86 ]. Furthermore, following IVH, extracellular Hb was found to be widely distributed in periventricular white matter and deposited in remote regions of the cerebellar white matter, leading to alteration of normal development of the cerebellar cortex [ 81 , 87 ].…”
Section: Hemolytic Conditionsmentioning
confidence: 99%